List of reviewers - Editorial Team, (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2025)
Thomas Biller, independent scholar, Freiburg/Breisgau, Germany Karl Borchardt, Monumenta Germaniae Historica, München Judith Bronstein, Department of Israel Studies, University of Haifa Marie-Luise Heckmann, Historisches Institut, Universität Potsdam Philippe Josserand, Département Histoire, Nantes Université Juhan Kreem, Tallinna Linnaarhiiv (City Archives of Tallinn) / Humanitaarteaduste instituut, Tallinna Ülikool (School of Humanities, Tallinn University) Rory MacLellan, The British Library, London Julia Możdżeń, Instytut Historii, Uniwersytet Gdański Klaus Neitmann, Historisches Institut, Universität Potsdam Piotr Oliński, Instytut Historii i Archiwistyki, Uniwersytet Mikołaja Kopernika w Toruniu Gregory O’Malley, independent scholar, Hugglescote, United Kingdom Julia Pavón Benito, Departamento de Historia, Historia del Arte y Geografía, Universidad de Navarra Magdalena Satora, Instytut Historii, Uniwersytet Kardynała Stefana Wyszyńskiego w Warszawie Marek Smoliński, Instytut Historii, Uniwersytet Gdański Maria Starnawska, Instytut Historii, Uniwersytet Przyrodniczo-Humanistyczny w Siedlcach Tomasz Torbus, Instytut Historii Sztuki, Uniwersytet Gdański Ewald Volgger, Institut für Liturgiewissenschaft und Sakramententheologie, Katholische Privat-Universität Linz